Determinan Tingkat Suku Bunga di Negara-Negara ASEAN - Dini Ardikaningtyas; Agung Riyardi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
Interest rates are the ratio of returns on a number of investments as a form of reward given to investors. The amount of interest rates varies according to the debtor's ability to provide a rate of return to creditors. The study aims to estimate the effect of economic growth, inflation, growth in the money supply, and export value on interest rates in ASEAN member states during 2016-2020 using the panel's data regression analysis. The results with the Common Effects approach show that the growth of the money supply has a positive effect on interest rates, while the value of exports has a negative effect on interest rates. Meanwhile, economic growth and inflation have no effect on interest rates in ASEAN member countries during 2016-2020.